2010
DOI: 10.1371/journal.pone.0013281
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine Clinical Failures in P. falciparum Malaria Are Associated with Mutant Pfmdr-1, Not Pfcrt in Madagascar

Abstract: Molecular studies have demonstrated that mutations in the Plasmodium falciparum chloroquine resistance transporter gene (Pfcrt) play a major role in chloroquine resistance, while mutations in P. falciparum multidrug resistance gene (Pfmdr-1) act as modulator. In Madagascar, the high rate of chloroquine treatment failure (44%) appears disconnected from the overall level of in vitro CQ susceptibility (prevalence of CQ-resistant parasites <5%) or Pfcrt mutant isolates (<1%), strongly contrasting with sub-Saharan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 34 publications
3
43
0
1
Order By: Relevance
“…The former accepted view revealed that the major role of CQ resistance was determined by polymorphisms in the pfcrt gene that encoded a transporter, which promoted drug efflux from the parasite digestive vacuole in its mutated forms, 8 whereas pfmdr-I mutation modulates the level of in vitro CQ resistance. 20 In our study, we combined in vitro and in vivo tests as well as molecular genotyping at pfcrt and pfmdr-I loci.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The former accepted view revealed that the major role of CQ resistance was determined by polymorphisms in the pfcrt gene that encoded a transporter, which promoted drug efflux from the parasite digestive vacuole in its mutated forms, 8 whereas pfmdr-I mutation modulates the level of in vitro CQ resistance. 20 In our study, we combined in vitro and in vivo tests as well as molecular genotyping at pfcrt and pfmdr-I loci.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between pfmdr-I genotypes and quinoline resistance has often generated conflicting results. It has been suggested that pfmdr-I 86Y can be correlated with increased CQ resistance in parasites that originated from different areas of the world, 7,8 but in India, field studies had not corroborated these findings, and the results of the P. falciparum genetic cross indicated that CQ resistance did not depend on the pfmdr-I gene. 12,21 Different groups of workers showed that, in India, CQ-resistant P. falciparum and the CQ treatment failure mainly occurred because of the mutation in the pfcrt and not the pfmdr-I gene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…trouve que nos données indiquent que certains marqueurs pertinents pour prédire la résistance aux antipaludiques dans certaines régions (comme l'Afrique par exemple) doivent être réévalués pour des contextes particuliers comme Madagascar [22] ou la Guyane française [23]. Ces données indiquent que l'évolution des populations parasitaires diffère dans différents contextes épidémiologiques et géographiques.…”
Section: Le Développement De Nouveaux Outilsunclassified